The Perception of Housekeeping Department StaffsToward Training Method at Golden Tulip Devins Hotel Seminyak. - Prabawa, Ida Bagus Junalaska; Sulistyawati, Agung Sri; Suarka, Fanny Maharani (Jurnal Kepariwisataan dan Hospitalitas; Vol 2 No 3 (2018): Vol.2,No.3,2018DO - 10.24843/JKH.2018.v02.i03.p10, 2019)
Golden Tulip Devins Hotel Seminyak is one of the accommodations 4 stars hotel that located in Jln. Petitenget, Seminyak, Bali. Companies should always held a job training to improve the service quality and to contribute their best to achieve the goals of the company. The formulation of the problem in this research is how housekeeping staff perception of the training methods in Golden Tulip DevinsSeminyak. The types and the sources of data used in this research are qualitative and quantitative data, while the sources data that used are primary and secondary data. The data collection techniques are observation, structured interview, literature studies and documentation. Mechanical determination sample saturated informants and the data analysis method used are descriptive analysis and Likert Scale. Based on the calculation using the Likert Scale of 36 respondents were asked their perception of assessment indicators of the housekeeping employee training method, which is the highest result are the perception from section Housekeeping Supervisor, Room Attendant and Linen Attendant with each section gain an average value are 4,25 and 4,24 that come under very well criteria. Meanwhile the lowest result are the perception from section Public Area Attendant with an average value is 4,02 that come under good criteria. Overall the employee perceptions that all training methods could improve the interpersonal skills so that employees are more responsible with the work that they have done. The suggestions that could be presented to the management of Golden Tulip Devins Hotel Seminyak are the job training is the important thing in the company to support a role in improving the quality of service so need to maintain. The frequency of job training was further enhanced in order to increase the skills and knowledge of employees and the company also should further develop the training materials that provided. Keywords : Perception, Training Method, Housekeeping Department Staff, Golden Tulip.